Financial Literacy and Financial Self Efficacy Towards Financial Technology in Increasing Financial Inclusion (Study of Students in Semarang City) - Hidayatullah, Suryakusuma Kholid; Rachmansyah DW, Yanuar (Journal of Economic Education, 2023)
This study aims to analyze the effect of financial literacy and financial self efficacy on financial technology in increasing student financial inclusion in the city of Semarang in the 2023 research period. In general, there are several factors that can affect the level of financial inclusion in understanding and recognizing aspects of financial technology, financial literacy and financial self-efficacy. In order to increase financial inclusion for the younger generation, this study emphasizes special analysis or studies related to what are the factors in supporting the increase in financial inclusion in the younger generation in the special aspects of respondents who are students. Data needs obtained from the results of questionnaire answers distributed to student respondents in the city of Semarang. The results of this study show that partially the variables of financial literacy and financial self-efficacy have a significant effect on financial technology. Partially, financial self-efficacy and financial technology variables have a significant influence on financial inclusion, while financial literacy variables are not significant on financial inclusion. The relationship of financial literacy to financial inclusion can be mediated by financial technology, while the relationship of financial self-efficacy to financial inclusion cannot be mediated by financial technology.